Splenic microRNA Expression Profiles and Integration Analyses Involved in Host Responses to Salmonella enteritidis Infection in Chickens - Li, Peng; Fan, Wenlei; Li, Qinghe; Wang, Jie; Liu, Ranran; Everaert, Nadia; Liu, Jie; Zhang, Yonghong; Zheng, Maiqing; Cui, Huanxian; Zhao, Guiping; Wen, Jie (Frontiers in Cellular and Infection Microbiology, 2017)
To understand the role of miRNAs in regulating genes involved in the host response to Salmonella enteritidis (SE) infection, next generation sequencing was applied to explore the altered splenic expression of microRNAs (miRNAs) and deregulated genes in specific-pathogen-free chickens. Birds were either infected or not (controls, C) and those challenged with SE were evaluated 24 h later and separated into 2 groups on the basis of the severity of clinical symptoms and blood load of SE: resistant (R, SE challenged-slight clinical symptoms and < 105 cfu / 10 μL), and susceptible (S, SE challenged-severe clinical symptoms and > 107 cfu / 10 μL). Thirty-two differentially expressed (DE) miRNAs were identified in spleen, including 16 miRNAs between S and C, 13 between R and C, and 13 between S and R. Through integration analysis of DE miRNAs and mRNA, a total of 273 miRNA-target genes were identified. Functional annotation analysis showed that Apoptosis and NOD-like receptor signaling pathway and adaptive immune response were significantly enriched (P < 0.05). Interestingly, apoptosis pathway was significantly enriched in S vs. C, while NOD-like receptor pathway was enriched in R vs. C (P < 0.05). Two miRNAs, gga-miR-101-3p and gga-miR-155, in the hub positions of the miRNA-mRNA regulatory network, were identified as candidates potentially associated with SE infection. These 2 miRNAs directly repressed luciferase reporter gene activity via binding to 3'-untranslated regions of immune-related genes IRF4 and LRRC59; over-expressed gga-miR-155 and interference gga-miR-101-3p in chicken HD11 macrophage cells significantly altered expression of their target genes and decrease the production of pro-inflammatory cytokines. These findings facilitate better understanding of the mechanisms of host resistance and susceptibility to SE infection in chickens.